2004
DOI: 10.1002/we.111
|View full text |Cite
|
Sign up to set email alerts
|

Grid impacts of wind power: a summary of recent studies in the United States

Abstract: Several detailed technical investigations of grid ancillary service impacts of wind power plants in the United States have recently been performed.These studies were applied to Xcel Energy (in Minnesota) and PacifiCorp and the Bonneville Power Administration (both in the northwestern United States). Although the approaches vary, three utility time frames appear to be most at issue: regulation, load following and unit commitment. This article describes and compares the analytic frameworks from recent analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
118
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(121 citation statements)
references
References 5 publications
0
118
0
1
Order By: Relevance
“…Denholm & Hand provide estimates of curtailment with no storage and with 24 hours of storage for the Electricity Reliability Council of Texas (ERCOT) region in the United States [8]. The seasonal fraction of total curtailment is quantified for each VRE share as the fraction of total curtailment that remains in the Denholm & Hand system with 24 hours of storage (i.e., the curtailment that is not addressed with shortterm storage) 4 . The seasonal fraction of curtailment increases from 15% at 50% VRE share to 35% at 100% VRE share and can only be addressed with seasonal storage, which in MESSAGE is represented by hydrogen electrolysis with seasonal storage.…”
Section: Electricity Curtailmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Denholm & Hand provide estimates of curtailment with no storage and with 24 hours of storage for the Electricity Reliability Council of Texas (ERCOT) region in the United States [8]. The seasonal fraction of total curtailment is quantified for each VRE share as the fraction of total curtailment that remains in the Denholm & Hand system with 24 hours of storage (i.e., the curtailment that is not addressed with shortterm storage) 4 . The seasonal fraction of curtailment increases from 15% at 50% VRE share to 35% at 100% VRE share and can only be addressed with seasonal storage, which in MESSAGE is represented by hydrogen electrolysis with seasonal storage.…”
Section: Electricity Curtailmentmentioning
confidence: 99%
“…For example, the integration of VRE is expected to entail more backup capacity to ensure peak demand is met, more flexibility to address increased fluctuations in power supply, and more storage and/or power-to-gas to absorb curtailment. The costs of implementing these structural and operational changes as well as the transmission upgrades required to accommodate VRE are termed integration costs and can be significant [3,4]. Hirth et al estimates the integration costs associated with a wind generation share of 30-40% to be 25-35 €/MWh, or as large as 50% of generation costs [5].…”
Section: Introductionmentioning
confidence: 99%
“…The intermittency of the renewable sources added to the grid up to the present time have been balanced by the dispatchable forms of electricity (mainly natural gas peaking plants) that currently sit ready to produce when the price incentivizes them to do so [7]. To integrate intermittent sources beyond some level of penetration, the grid will require new balancing capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of backup dispatchable power required to balance an intermittent source is unclear, especially in light of the complications associated with transmission availability. Preliminary estimates of the cost of integration vary from 0.006 USD/kWhr for 20% penetration to 0.0018 USD/kWhr for 4% penetration [7]. Even the low-cost estimates Figure 1: (A) The normalized shape of wind power calculated from real wind speed data in Wilhelminadorp, Netherlands, by applying the power curve for a GE 1.5MW turbine [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…10 A review of studies on the impact of wind power integration in some US utilities has indicated the signifi cance of wind power forecasting in reducing the imbalance costs and the spinning reserve requirements. 11 For example, in December 2000, Southern California Edison saved $2 million in imbalance costs by improving its wpf. 12 A similar study deals with the importance of short-term wind power prediction in the participation of wind power in electricity markets in Spain 13 and other European countries.…”
Section: Introductionmentioning
confidence: 99%